A preliminary study: effect of local honey on spermatogenesis in rats - Mohamed, Mahaneem (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2010)
The aim of this study was 1o evaluate the effect of different doses of Malaysian honey on male reproductive parameters in adult rats. Thirty-two healthy adult male Sprague-Dawley rats were randomly divided into 4 groups (8 rats per group). Group 1 (control group) was given 0.5 ml of distilled water. Groups 2, 3 and 4 were given 0.2, 1.2 and 2.4 g kg·' body weight of honey, respectively. The rats were treated orally by gavage once daily for 4 weeks. Honey did not significantly alter body and male reproductive organs weights. The rats in Group 3 which received honey at 1.2 g kg· had significantly higher epididymal sperm count than those in Groups 1, 2 and 4. No significant differences were found for the percentage of abnormal sperm, elongated spermatid count, reproductive hormonal levels as well as the histology of the testis among the groups. In conclusion, Malaysian honey at a dose of 1 .2 g kg·' daily significantly increased epididymal sperm count without affecting spermatid count and reproductive hormones. These findings might suggest that oral administration of honey at this dose for 4 weeks may enhance spermiogenesis in adult rats